SOCIAL MEDIA AND MIGRATION DECISION-MAKING PROCESSES OF INDONESIAN HIGHLY SKILLED MIGRANT IN THE MIDDLE EAST COUNTRIES - Hidayati, Inayah (UNIVERSITAS PAKUAN, 2020)
This research aims to explain the impact of social media on the migration decision-making process of Indonesian highly skilled migrants who used a social media account. In detail, this research will consider the role of social media in the migration decision-making process of highly skilled migrants who emigrated from Indonesia and how they use social media in the context of the migration decision-making process. Methods: The data collected included qualitative data from in-depth interviews. Expectation: 1).Social media help highly skilled migrants on migration decision making process. 2).Highly skilled migrants use social media for searching information about destination area. Result: Highly skilled migrant in the Middle East Countries use their social media to gain information before they choose their destination country. They use social media to making contact with their friends and colleague in the destination country.